PENGARUH INTRADIALYTIC EXERCISE TERHADAP FATIGUE PADA PASIEN HEMODIALISA : LITERATURE REVIEW - Nurmansyah, Nurmansyah; Arofiati, Fitri (Jurnal EDUNursing, 2019)
Chronic kidney failure is a multidimensional health problem in various countries with increasing prevalence in every years. Hemodialysis is a recovery therapy that functions in the blood. Hemodialysis must be carried out throughout life until receive a new kidney transplant. As many as 70% -90% of patients with chronic kidney failure complain of fatigue in hemodialysis. Complaints of fatigue in patients with kidney failure in hemodialysis cannot be ignored. Excessive fatigue in patients can cause prolonged complications and affect quality of life. This research method uses a literature review technique. Data collection through research on the internet using Google Scholar, PubMed, and Proquest with key words intradialytic exercise, fatigue, and hemodialysis. The results with the keywords entered were 2,449 research journals. Then do the screening process and get 10 journals are in accordance with the criteria of discussion. From the results of a review, intradialytic exercises has an impact to the level of fatigue. In addition, intradialytic exercise also provides an increase physical improvement, increased blood pressure and serum electrolytes, improved quality of life and improved sleep quality. In applying intrdialytic exercises, it is proven effective and simple to do in dealing with complaints of patients who need hemodialysis and do not require additional costs. Some types of intradialitic exercises that can be used are Qigong Training, Deep Breathing Exercises, Leg Ergometry Exercises, Intradialitic Acute Therapy Exercises (I-ACETD), Strengthening Exercises, Regular Flexibility, Range of Motion Exercises. Keywords: intradialytic exercise, fatigue, hemodialyis